Working Capital Management and Profitability in IT And Telecom Industry in India - Singh, D. P. (Indian Journal of Finance, 2012)
The study investigated the relationship between working capital management and profitability in the firms belonging to IT and telecommunication industry in India. 11 firms were randomly selected,out of which, 05 belong to information technology industry and the remaining are from the telecommunication industry. The researcher took the return on capital employed as a measure of profitability. And other variables for studying working capital management were working capital turnover, current ratio, days’ inventory outstanding, days’ sales outstanding, days’ payable outstanding and cash conversion cycle. The researcher collected financials of the companies for 12 years from 1999 to 2010. Therefore, in all, 132 firm year observations (after pooling cross section and time series data) were used for the study. The researcher carried out descriptive statistics and correlation analysis using SPSS. The results show a positive relationship between working capital turnover, current ratio, sales to total asset ratio and profitability. Day’s inventory outstanding shows a negative relationship with profitability. Relationship of current ratio with profitability, which is positive, is a departure from past studies.